ANALISIS POSITIVE DEVIANCE: POLA MAKAN YANG MEMPENGARUHI KEJADIAN ANEMIA PADA IBU HAMIL DI KOTA YOGYAKARTA - Ika Mustika Dewi; Prastiwi Putri Basuki; Siti Uswatun Chasanah; Andri Purwandari (Jurnal Delima Harapan, 2021)
Introduction: Anemia is a public health problem associated with an increased of morbidity and mortality. Poor eating habits during pregnancy will cause the body's need for nutrients both micro and macro is not met, so will result in malnutrition and anemia. Methods: It was observational study using a cross sectional design. Sampling was done by purposive sampling methods. This dietary data accumulation was done by using Food Frequency Questionnaire. In-depth interviews was used to explore positive eating habit in pregnant women that are not anemic. Hemoglobin was detected by using HemoCue analyzer. Statistical analysis of data was used the Chi Square test. Results: The results show that 88.2% of the pregnant women are not anemic, 64.5% of pregnant women often consume enhancers, and 57.9% of pregnant women rarely consume inhibitors. There was no correlation between consumption of enhancer with anemia (p = 0.478). There was no correlation between consumption of inhibitors with anemia (p = 1,000). Positive eating habits of pregnant women who are not anemic is often consume foods high in vitamin C and animal protein. Conclusion: There was no correlation between consumption of enhancher and inhibitor with anemia incidence among pregnant women Recomendation: Improved health promotion of positive eating habit to prevent anemia in pregnant women